Integrated bioinformatics analysis of expression and gene regulation network of COL12A1 in colorectal cancer - Yibin Wu; Ye Xu (Cancer Medicine)
Abstract The extracellular matrix (ECM) is reported to be involved in tumorigenesis and progression. Collagen IIX is a major ECM protein. Abnormal COL12A1 expression is associated with carcinogenesis of colorectal cancer (CRC), but its clinical value and function have not yet been analyzed. Expression, methylation, and survival were analyzed by using Oncomine, UNCLA, and GEPIA, while COL12A1 alterations and related functional networks were identified using cBioPortal. The gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes pathways（KEGG）of COL12A1 in CRC were explored using LinkOmics. Gene set enrichment analysis (GSEA) examined target networks of kinases, miRNAs, and transcription factors. We found that COL12A1 was overexpressed in CRC and the COL12A1 gene was often amplified in CRC. Survival analysis revealed that patients with higher COL12A1 expression had a poor prognosis. Expression of COL12A1 was linked to functional networks via regulating pathways involving focal adhesion, PI3K‐Akt signaling pathway, and ECM‐receptor interaction. Functional network analysis suggested that COL12A1 regulated integrin binding, collage binding, and extracellular matrix structural constituent via pathways involving some several cancer‐related kinases, miRNAs, and transcription factor. Furthermore, other FACITs genes (COL1A2, COL3A1, COL5A1, COL5A2, and COL6A3) for ECM in correlation with COL12A1 were identified to be related with the prognosis in CRC. These results suggested that the distinct fibril‐associated collagens with interrupted triple helices (FACITs) genes may serve as prognostic and therapeutic biomarkers of CRC in the future.